2020
DOI: 10.3892/ol.2020.11958
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA CCAT2 promotes prostate cancer cell proliferation and invasion by regulating the Wnt/β‑catenin signaling pathway

Abstract: Long non-coding RNA colon cancer associated transcript 2 (CCAT2) is dysregulated in a number of different types of human cancer, and affects cancer progression via the Wnt/β-catenin signaling pathway. However, the roles of CCAT2 and the Wnt/β-catenin signaling pathway in prostate cancer (PCa) are not completely understood. The present study aimed to investigate the potential mechanism of CCAT2 in PCa. In the present study, the reverse transcription-quantitative PCR (RT-qPCR) results indicated that CCAT2 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…This interplay between CCAT2, MYC, and WNT molecules has been explored and confirmed in multiple cancers in recent years and is responsible for the main pro-tumorigenic roles of CCAT2. Similar studies confirmed the presence of the mechanism in the case of thyroid [27], ovarian [28], clear cell renal cell carcinoma [29], and breast cancers [30].…”
Section: Myc and Wnt Pathway Activationsupporting
confidence: 77%
“…This interplay between CCAT2, MYC, and WNT molecules has been explored and confirmed in multiple cancers in recent years and is responsible for the main pro-tumorigenic roles of CCAT2. Similar studies confirmed the presence of the mechanism in the case of thyroid [27], ovarian [28], clear cell renal cell carcinoma [29], and breast cancers [30].…”
Section: Myc and Wnt Pathway Activationsupporting
confidence: 77%
“… 9 LncRNA CCAT2 initiates prostate cancer proliferation and metastasis through activation of Wnt signaling. 10 LncRNA LINC00491 promotes lung cancer proliferation, migration and invasion by sponging miR-324 to facilitate SP1 expression. 11 Thus, it is important to determine the correlation between lncRNA and RB progression.…”
Section: Introductionmentioning
confidence: 99%
“… 11 In prostate cancer, knockdown of CCAT2 reduced Wnt/β-catenin signaling by inhibiting the expression of TCF7L2. 29 Cai et al. reported that suppressing the expression of CCAT2 in breast cancer cells decreased the translational levels of β-catenin both in the cytoplasm and nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…11 In prostate cancer, knockdown of CCAT2 reduced Wnt/b-catenin signaling by inhibiting the expression of TCF7L2. 29 Cai et al reported that suppressing the expression of CCAT2 in breast cancer cells decreased the translational levels of b-catenin both in the cytoplasm and nucleus. 13 Guo et al reported that knockdown of CCAT2 in glioma cells suppressed b-catenin translocation from the cytoplasm to the nucleus, while there was little effect on the total cellular b-catenin levels.…”
Section: Discussionmentioning
confidence: 99%